The role of the receptor PD1 in regulating tumor-specific T cell accumulation in atherosclerotic mouse aortas - Ericsson,Astrid (2025)
Atherosclerosis, the formation of inflammatory plaques in the arterial walls, is the most common underlying cause behind cardiovascular disease (CVD). The risk of atherosclerosis has been shown to increase following immune checkpoint inhibitor therapies such as anti-PD1. Anti-PD1 therapy has revolutionized cancer treatment as it blocks the immune checkpoint receptor PD1, preventing T cell exhaustion and restoring cellular functionality in T cells after prolonged antigen stimulation. While this is beneficial against persistent tumors, it is also known to cause increased CD8 T cell accumulation in atherosclerotic plaques and promote atherosclerotic inflammation and progression. Whether or not these CD8 T cells are autoreactive to antigens within the plaque is unknown. In this study, we aimed to investigate whether tumor-specific T cells can infiltrate atherosclerotic plaques following treatment of anti-PD1. We performed an adoptive transfer of OVA-tumor specific OT-I CD8 T cells, followed by anti-PD1 administration, to T cell receptor α deficient, atherosclerotic mice harboring OVA-expressing tumors. Our results suggest that tumor specific CD8 T cells occur in the atherosclerotic aorta of tumor bearing mice, and that anti-PD1 treatment increases the level of PD1-expression on aortic CD8 T cells, demonstrating that anti-PD1 therapy can impact the phenotype of tumor-specific T cells located in the aorta. These findings pave the way for further investigation into how PD1 blockade affects atherosclerosis, and for the study of CD8 T cell specificity in atherosclerosis in general.